Geochemical Characteristics and Genesis of Cambrian Shale Gas in the Southern Margin of Hannan Ancient Uplift - Guo, Tianxu; Chen, Xianglin; Ge, Mingna; Wang, Chao; Bao, Shujing; Shi, Dishi (Frontiers in Earth Science, 2022)
The geological characteristics of shale and the gas composition, carbon isotopic variation from the shale are very important indicators for shale gas study. This paper analyzed the geological characteristics of Cambrian Niutitang shale, and focuses on the gas composition and carbon isotopic characteristics of the shale gas from the Cambrian Niutitang Formation. We can see that the total organic carbon content range from 0.41% to 4.29%, with an average of 1.65%, which is mainly type I and Ⅱ1. The thermal maturity of sample range from 1.98% to 2.53%, with an average of 2.30%, which is in the post mature stage of thermal evolution. The Cambrian Niutitang Formation shale gas in the southern margin of the Hannan ancient uplift is high-quality hydrocarbon gas, the methane takes an absolute majority with a content from 89.60% to 99.19% with an average of 96.46%. The wetness of the gas from the study area range from 0.06% to 0.42%, with only 0.25% on average, which is defined as typical dry gas. The distribution of carbon isotope values has partial "reverse" characteristics that is δ13C1＞δ13C2, δ13C2＜δ13C3. The natural gas of Niutitang Formation in the study area belongs to thermogenic gas. At the same time, it is found that some data points are beyond the range of thermogenic gas, which is mainly due to the low humidity and heavy carbon isotope value of methane caused by the high maturity of source rock. In the study area the Niutitang Formation natural gas carbon isotope values of are located in the Zone III with the characteristics of mixed reversal gas in the δ13C1-δ13C2 part.